PENYELESAIAN KREDIT MACET DENGAN PENGALIHAN PIUTANG SECARA CESSIE DI KOTA PEKANBARU - Tiara Antika; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The Republic of Indonesia is a state of law, where the law elaborated by the government through the establishment of legislation has a very important role in regulating and directing the lives of its people so as to create an orderly life system that is just, prosperous and peaceful. Laws are created because humans live together and can only live together, by making concepts that are very appropriate and meritorious in human life that prioritizes their rights to society related to other interests. In ensuring justice, certainty and legal usefulness for every citizen, the state has the obligation to provide protection to anyone on any issues that intersect with the law, including the problem of cessie. However, in its implementation there were many violations of the law concerning cessies, such as violations of the law in the settlement of bad loans. There are many instances where a new creditor necessarily has to have a debtor's debt guarantee if the debtor defaults which causes losses to the debtor. The purpose of writing this thesis, namely; First, knowing the efforts that new creditors can make in the process of settling bad debts, Second; know the implications of the application of Article 12 of the Underwriting Rights Law concerning the prohibition of beding for the settlement of bad loans in Pekanbaru City. From the results of the research based on two problem formulations, it can be concluded, First, the efforts made by new creditors in the process of settling bad loans related to the prohibition of beding namely: new creditors can execute through the court against debtor debt collateral, parate execution and collateral object execution. Second, the implication of the application of Article 12 of the Underwriting Rights Law concerning the prohibition of beding on the settlement of bad loans, namely: the obstruction of the settlement of bad credit by new creditors (cessionaris), making it difficult for creditors to get the right to the receivables they have agreed in the credit agreement, giving losses to new material and non-material creditors. Keyword: Settlement-transfer of accounts receivable-cessie